Owner perception of health of North American dogs fed meat- or plant-based diets. (December 2022) - Dodd, Sarah; Khosa, Deep; Dewey, Cate; Verbrugghe, Adronie
Abstract: Background: Some dog owners elect to feed their dog a plant-based food either as part of or for their entire dietary intake. Being omnivores or facultative carnivores, a strictly plant-based diet is not the natural type of food dogs evolved to consume, leaving some question as to whether this feeding management strategy is safe and healthy for dogs. Objectives: This study surveyed owner perceptions of health and wellbeing of dogs and compared between those fed meat-based and plant-based diets. Methods: A web-based questionnaire was distributed to pet owners to collect data on dog characteristics, husbandry, health and wellbeing. Univariate comparisons between diet groups was made by chi square analyses or Kaplan-Meier tests as appropriate, with a significance cut-off value of 0.05. Multivariate models were negative binomial and logistic regression for count and categorical data, respectively. Results: Owners feeding plant-based diets to their dog reported fewer health disorders, specifically with respect to ocular or gastrointestinal and hepatic disorders. Dog longevity was reported to be greater for dogs fed plant-based diets. Owners feeding plant-based diets to their dogs relied less on veterinary associates for nutrition information, versus dog owners feeding meat-based diets. Conclusions: Dog owners feeding a plant-based diet did not perceive adverse health effects in their dogs. The results might suggest an association between feeding a plant-based diet and perceived health and longevity, however inherent bias and limitations associated with surveys of owner perception must be considered, and objective research is required to determine if plant-based diets truly affect canine health. Highlights: Dog owners report no adverse health outcomes attributable to being fed a plant-based diet. Fewer ocular or gastrointestinal and hepatic disorders reported in dogs fed plant-based diets. Longevity of dogs reported to be longer in dogs fed plant-based.